Faktor-faktor yang Mempengaruhi Mahasiswa Akuntansi dalam Memilih Jurusan Akuntansi di Universitas Pembangunan Panca Budi - Vina Arnita (Universitas Negeri Medan, 2021)
The purpose of this study is to empirically prove the effect of education costs, interest and motivation on the choice of accounting majors. This research was conducted on accounting students at Pemabangunan Panca Budi University, Medan. This research uses associative quantitative research. The data analysis technique used is the classical assumption test, multiple linear regression test, and the coefficient of determination (Adjusted R Square). The basis for sampling in this study using saturated samples (census) with a total sample of 300 respondents. The results of this study indicate that partially the cost of education interest and motivation have a significant effect on the choice of accounting department. This can be seen in the results of the coefficient of determination (Adjusted R Square), which means that the variability of the dependent variable which can be explained by the independent variable is 65,3%. While the remaining 34,y% is explained by other variables that are not included in the regression model.